Prevalence of Hepatitis B & C in a General Population - Kosar Aziz, Samia Sarwar, Iram Qamar, Farrukh Sarfraz, Noor Ul Ain (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Hepatitis is characterized by the inflammation of the liver creating swelling and in numerous cases permanent damage to liver tissue. The foremost common types of Hepatitis are Hepatitis A, B, and C. Both Hepatitis B and C can lead to lasting liver damage and in numerous cases ‘death’. In all over the world around 300 million individuals are contaminated with hepatitis B infection, and 75% of Hepatitis C infection. The significance of hepatitis B and hepatitis C is outlined by the truth that these infections are forcing a overwhelming burden on national economy and person families due to considerable morbidity and mortality from both acute contamination and persistent sequelae including chronic hepatitis, cirrhosis and hepatocellular carcinoma. Objective: To determine the frequency of Hepatitis B & C in a general population of Rawalpindi Material and Methods Study Design: Quantitative cross sectional Duration: Three months i.e. 1st January 2022 to 30th March 2022 Data Collection procedure: There were 400 subjects were reported in two different regions of Rawalpindi in a free medical camp in which 241 were males and 159 were females. All subjects were asked about previous screening of hepatitis B & C and family history regarding any previous infection. After taking informed consent and briefing collect the blood sample in a tube. Results: Among 400 subjects the overall prevalence of Hepatitis B and C was 6.4%. 2.4% males and 1.2% females were in HBV infection whereas 1.6% males and 1.2% females in HCV infection. Conclusion: This study audits predominance of HBV and HCV in two different ranges of Rawapindi Pakistan, along with awareness status, risk factors in Pakistani population. Prevalence of HBV and HCV contamination shifts with population residing totally different regions of Pakistan.